PHYSICAL TRAINING IN SOCIAL SPHERE OF STUDENT YOUTH - Ігор Шеремет (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The notion of physical culture and sport has been disclosed in the article. The importance and impact of the latter on human organism have been determined. There has been analyzed the necessity of taking up physical exercises in the age group of students, as this is a period when human organism continues its development. Having analyzed theoretical information, there have been pointed out the factors that influence healthy regime. The article therefore stresses the importance of individual exercises, as well as forming the habits that would ensure the development of student's personality.